Acoustophoretic microfluidic chip for sequential elution of surface bound molecules from beads or cells - Augustsson, Per (American Institute of Physics, 2012)
An acoustophoresis-based microfluidic flow-chip is presented as a novel platform to facilitate analysis of proteins and peptides loosely bound to the surface of beads or cells. The chip allows for direct removal of the background surrounding the beads or cells, followed by sequential treatment and collection of a sequence of up to five different buffer conditions. During this treatment, the beads/cells are retained in a single flow by acoustic radiation force. Eluted peptides are collected from the outlets and subsequently purified by miniaturized solid-phase extraction and analyzed with matrix assisted laser desorption mass spectrometry. Fundamental parameters such as the system fluidics and dispersion are presented. The device was successfully applied for wash and sequential elution of peptides bound to the surface of microbeads and human spermatozoa, respectively.